Administrative Role in Improving School Administrative Services (Peran Tata Usaha dalam Peningkatan Layanan Administrasi Sekolah) - Widyawati Kahar; Badarwan Badarwan (Shautut Tarbiyah, 2023)
This article aims to analyze the role of administration in improving school administration services. The research was conducted at SMA Negeri 1 Konawe Selatan, using a qualitative research type with a narrative approach. Data collection techniques were carried out by observation, interviews and documentation. Data analysis was carried out through data reduction, data presentation and drawing conclusions. The technique of checking the validity of the data was carried out using the triangulation method (source, technique, and time). The results showed: 1) Administrative services at SMA Negeri 1 Konawe Selatan include curriculum administration services, student administration services, public relations administration services and facilities and infrastructure administration services. 2) Administration plays an important role in providing curriculum administration services, facilities and infrastructure administration services, public relations administration services, and student administration services.Keywords:     Administrative Governance, School Administration Services